Inelastic neutron scattering study of binding of para-hydrogen in an ultra-microporous metal-organic framework - Yang, Sihai; Ramirez - Cuesta, Anibal J.; Schröder, Martin (Elsevier, 2014)
Metal-organic framework (MOF) materials show promise for H2 storage and it is widely predicted by computational modelling that MOFs incorporating ultra-micropores are optimal for H2 binding due to enhanced overlapping potentials. We report the investigation using inelastic neutron scattering of the interaction of H2 in an ultra-microporous MOF material showing low H2 uptake capacity. The study has revealed that adsorbed H2 at 5 K has a liquid recoil motion along the channel with very little interaction with the MOF host, consistent with the observed low uptake. The low H2 uptake is not due to incomplete activation or decomposition as the desolvated MOF shows CO2 uptake with a measured pore volume close to that of the single crystal pore volume. This study represents a unique example of surprisingly low H2 uptake within a MOF material, and complements the wide range of studies on systems showing higher uptake capacities and binding interactions.